Luzhou‐Feier powder reduces inflammatory response and improves intestinal immune barrier in rats with severe acute pancreatitis. Issue 10 (21st August 2021) - Huang, Zhiwei; Guo, Xiaodong; Tan, Peng; Wang, Min; Chen, Hao; Peng, Yan; Xia, Xianming; Tang, Xiaowei; Li, Qiu; Fu, Wenguang
Abstract: As we know, nutritional support plays a key role in the treatment of severe acute pancreatitis (SAP). Since total parenteral nutrition (TPN) was discovered, the mortality of SAP had been greatly reduced. But researchers recently demonstrated that the prognosis of SAP could be improved by early enteral nutrition (EEN), which has been a priority for nutritional support in patients with SAP. However, implementation of total enteral nutrition is often challenging in the early stage of SAP. If the enteral nutrition is overused, the burden on the gastrointestinal tract will be aggravated. Under such circumstances, the combination of enteral and parenteral nutrition for nutritional support of SAP patients would be a better choice. Therefore, in this study, we compared the efficacy of two enteral nutrition agents: traditional nutritional supplement named Luzhou‐Feier powder (LZ‐FP) and enteral nutritional suspension (TPF) combined with parenteral nutrition to total parenteral nutrition (TPN) in the treatment of SAP rats. Our analysis revealed that the combination of enteral nutrition and parenteral nutrition was more effective than TPN in SAP. And LZ‐FP met the requirements for enteral nutrition of SAP supporting its clinical application in SAP. Practical applications: Luzhou‐Feier powder (LZ‐FP) is a traditional Chinese nutritional supplement that was originally developed as a nutritional supplement for infants and is currently used for nutritional support in patients with chronic and consumptive diseases. Our research investigated the effect and its possible mechanisms of LZ‐FP as early trophic enteral nutrition in SAP rats and compared it with TPF and TPN which have been used clinically. We found that LZ‐FP helped to reduce inflammatory response and improve the intestinal immune barrier of SAP. The curative effect of LZ‐FP was comparable to that of TPF. And this effect may be achieved by inducing the secretion of gut hormones. Our research indicates that LZ‐FP should be considered as an enteral nutrition preparation for SAP. Abstract : In this study, we found that Luzhou‐Feier powder (LZ‐FP), a traditional Chinese nutritional supplement, helped to reduce inflammatory response and improve the intestinal immune barrier of severe acute pancreatitis (SAP). The results indicated that LZ‐FP should be considered as a novel enteral nutrition preparation for SAP.